The use of magnetic coercivity method to diagnose crane metalware - Starikov, Maxim; Beljatynskij, Andrey; Prentkovskis, Olegas; Klimenko, Irina (Transport, 2011)
The recent problem of estimating the residual life of metal structures for handling equipment is actual, since more than 90% exhausted its regulatory resources. The current paper proposes an approach to solve this problem by using the coercive force. It is shown that in order to determinate damage of dangerous element of crane it is needed to know not only a coercive force but also a stress. Mathematical model is proposed to determine the damage of metal ware. First Published Online: 05 Oct 2011